God's architect : Pugin and the building of romantic Britain - Hill, Rosemary (Yale University Press, 2009)
God's Architect is the first modern biography of Augustus Welby Northmore Pugin (1812-1852), one of Britain's greatest architects. The author draws on thousands of unpublished letters and drawings to recreate Pugin's life and work as architect, propagandist, and Gothic designer, as well as the turbulent story of his three marriages, the bitterness of his last years, and his sudden death at forty. -- Inside cover.